2017
DOI: 10.1007/s11085-016-9706-0
|View full text |Cite
|
Sign up to set email alerts
|

A Thermodynamic Approach to Guide Reactive Element Doping: Hf Additions to NiCrAl

Abstract: A method based on thermodynamic modeling was developed to determine optimal amounts of Hf additions to Al 2 O 3-forming, γ-γ NiCrAl alloys. The alloy ability to maintain Hf in solution was set by the Hf concentration required to form HfO 2 at the oxygen activity defined by the alloy/Al 2 O 3 equilibrium. This Hf tolerance decreased with increasing temperature and increased with increasing γ fraction. The latter was due to the higher solubility of Hf in γ , compared to γ. The validity of the procedure was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…It should be noted that, both qualitatively and quantitatively, the results obtained are consistent with those reported by other authors in terms of the following: (1) The k p values of Si-containing alloy were close to that observed for Ni15Cr5Al + Si (1 wt%) [17]; (2) Si additions resulted in reaching the steady-state oxidation earlier (shortened transient oxidation stages) [17]; (3) Hf additions, if exceeding the solubility limit (over-doping), form oxide precipitates in the underlying substrates as well as in the scales [6,7,14,15,19]. Comparison of the results obtained with those in an extensive study of the effect of Hf, Y and Si additions on the oxidation behavior of Ni20Al5Cr alloy and René N5 superalloy reported elsewhere [11] led to some discrepancies that need further investigation involving the effect of Cr and the content of the additions.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…It should be noted that, both qualitatively and quantitatively, the results obtained are consistent with those reported by other authors in terms of the following: (1) The k p values of Si-containing alloy were close to that observed for Ni15Cr5Al + Si (1 wt%) [17]; (2) Si additions resulted in reaching the steady-state oxidation earlier (shortened transient oxidation stages) [17]; (3) Hf additions, if exceeding the solubility limit (over-doping), form oxide precipitates in the underlying substrates as well as in the scales [6,7,14,15,19]. Comparison of the results obtained with those in an extensive study of the effect of Hf, Y and Si additions on the oxidation behavior of Ni20Al5Cr alloy and René N5 superalloy reported elsewhere [11] led to some discrepancies that need further investigation involving the effect of Cr and the content of the additions.…”
Section: Discussionsupporting
confidence: 65%
“…The two-phase γ/γ′ Ni-Al-based alloys, mostly γ/γ′-type ones, alloys that usually contain also Pt, are considered as promising high-temperature coating materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Their oxidation resistance can be improved by additions of reactive elements * Jerzy Jedliński jedlinsk@agh.edu.pl Extended author information available on the last page of the article (e.g., Hf, Y), due to the well-evidenced, so-called, reactive-element-effect, reviewed elsewhere [21][22][23], while the effect of silicon additions is still under investigation [11,14,17]. However, in order to optimize the beneficial effect of the reactive elements in qualitative and quantitative terms, as well as to examine the effect of Si, the oxidation behavior should be elucidated as a function of the additions (or their combinations), their amounts and exposure conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The link between primary reaction modes identified using unary or binary de- Figure 13: Map showing the effect of sulfate-oxide deposits on the oxidation of NiCoCrAlY alloys at 1100 • C. The boundaries were determined from work by Giggins and Pettit [36] and our work [38] on NiCrAl alloys. "NiO" denotes alloy compositions which form external NiO and internal Al 2 O 3 and Cr 2 O 3 ; "Cr 2 O 3 " denotes compositions which form external Cr 2 O 3 and internal Al 2 O 3 ; "Al 2 O 3 " denotes compositions which form external Al 2 O 3 exclusively; "transition" denotes compositions subject to localized internal oxidation of Al.…”
Section: Discussionmentioning
confidence: 99%
“…4.31. where R is the gas constant, T is the absolute temperature, Ni-Cr-Al alloys. They further suggested that the level of hafnium content varies due to structural changing of alloy subsurface region by the selective oxidation of aluminium because  dissolution in the substrate [64]. Thus, the factors which may control the activities of aluminium and reactive elements are expected to affect the optimised concentration of reactive elements.…”
Section: Effect Of Reactive Elementsmentioning
confidence: 99%